Effect of the metallicity of the intergalactic medium in the Lyman‐α forest correlation function. Issue 1 (20th March 2023) - Muñoz‐Gutiérrez, Andrea; de la Macorra, Axel
Abstract: The Lyman‐ α (Ly α ) forest allows to constraint cosmological parameters at redshifts above 1.8 $$ 1.8 $$ using the technique of standard rulers determined by baryon acoustic oscillations. This makes it an important tracer for the study of the universe at high redshift. For this work, several synthetic datasets have been generated to understand the astrophysical effects and contaminants that contribute to the shape of the Ly α flux correlation function, and to be able to reproduce the correlation function measured with data spectra from different galaxy surveys (extended Baryon Oscillation Spectroscopic Survey and Dark Energy Spectroscopic Instrument). Among these phenomena the presence of metals in the intergalactic medium translate into an important bias in the flux correlation function with respect to the flux correlation function calculated considering an only Hydrogen in the intergalactic medium. In this work we study the influence of the metallicity in the Ly α flux correlation function, simulating the presence of four Silicon transitions in synthetic spectra developed in preparation for the Dark Energy Spectroscopic Instrument and compared with the data obtained in the 14th data release of the extended Baryon Oscillation Spectroscopic Survey. These results were used for the analysis of the 16th data release of the extended Baryon Oscillation Spectroscopic Survey, and are currently being used for the analysis of the first data release of the Dark Energy Spectroscopic Instrument survey.